Interrelation of growth/differentiation factor-15 level with laboratory and clinical and functional parameters of patients with coronary artery disease - E. A. Zakharyan (Кардиоваскулярная терапия и профилактика)
Growth differentiation factor 15 (GDF-15) is a circulating protein that is associated with various pathological conditions.Aim. To study the relationship between the level of GDF-15 and laboratory, clinical and functional parameters of patients with coronary artery disease (CAD).Material and methods. All patients with coronary artery disease underwent a general clinical examination, coronary angiography, extracranial artery ultrasound examination, echocardiography, determination of the serum level of GDF-15 (ng/ml) and matrix metalloproteinase 9 (ng/ml). Statistical processing of the obtained results was carried out using the Statistica 10.0 software.Results. The study included 88 people (55 men and 33 women), 78 of whom were patients with an established diagnosis of CAD and 10 were healthy volunteers (control group). In the group of CAD patients, the median level of GDF-15 was 4,98 ng/ml [3,15; 8,24], while in the control group — 1,95 ng/ml [0,01; 2,45]. An association of GDF-15 concentration with the age of patients was found (r=0,44; p<0,001). There was a direct correlation between the level of GDF-15 and interventricular septal thickness (r=0,33; p<0,05), heart failure stage (Strazhesko-Vasilenko classification) (r=0,23; p<0,05), the concentration of matrix metalloproteinase 9 (r=0,24; p<0,05), carotid intima-media thickness (r=0,28; p<0,05), the number of coronary arteries that required revascularization during coronary artery bypass grafting (r=0,52; p<0,05), and multifocal atherosclerosis (r=0,23; p<0,05). In patients with atherosclerotic lesions in 2 or 3 vascular beds, the level of GDF-15 was significantly higher than in patients with CAD (p<0,05).Conclusion. The results obtained demonstrate the value of GDF-15 as a potential marker of atherosclerotic vascular changes, the severity of myocardial hypertrophy, and the severity of heart failure.